The production function socialization trend of rural housing land and its response to rural land planning in metropolitan suburbs from the perspective of rural space commodification - Zhao, Qinglei; Jiang, Guanghui; Ma, Wenqiu; Yang, Yuting; Zhou, Tao (Frontiers in Environmental Science, 2022)
Investigating the production function change of rural housing land is important to guide appropriate land use adjustment and rural land planning. Taking into account the layout characteristics from 2005 to 2018, employing structural equation model and the theory of planned behavior to analyze the differentiation mechanism of rural housing land production function based on survey data of 613 typical farmers in Pinggu District of Beijing. The results show that: (1) The production function intensity of rural housing land in Pinggu District from 0.327 to 0.126, and the coefficient of variation increased from 0.15 to 0.54, indicating that the overall production function decreased but the spatial heterogeneity increased. (2)The production function of rural housing land gradually withdrew and socialized in villages, following the socialization evolution process of agricultural production function, industrial and commercial service function, and public service function. (3)The internal land use pattern of rural housing land is significantly influenced by the subjective norms and perceptual behavior control of farmers. The demonstrative norms of family and the prescriptive norms of village collective have significant effects on subjective norms, and the perceived behavioral control is significantly affected by income scale and structure, family size, and employment type. (4) To further promote the rural housing land management, it is necessary to optimize its prescriptive norms of the village collective, improve farmers' income level and employment structure, and weaken farmers' perceived difficulty. According to the different function socialization stages of rural housing land, the rural land planning should coordinate the relationship between the production function socialization of rural housing land and the commercialization of rural space, and boost the revitalization of rural industry.